Cultural priming effect in dyadic negotiation. - Chong, Yen Ling. (2008)
This study seeks to study the cultural priming effect on negotiation amongst bicultural individuals, Singaporean Chinese in particular, and their choice of negotiation tactics and behaviours. A two-part experimental study (a priming task followed by a negotiation simulation task) was carried out.